بائبل سے گریز کرنے کا نبوی حکم (اسنادی حیثیت، حکمت ومفہوم اور متعلقہ مباحث): The Prophetic Command to Avoid the Bible (Authenticity, Wisdom, Meaning and Relvent Discussions) - Abdullah Shariq, Muhammad (FIKR-O NAZAR فکر ونظر, 2024)
According to some hadiths, Prophet Muhammad (peace and blessings of Allah be upon him) forbade one of his companions, Hazrat Umar bin Khattab, from studying the Bible. These hadiths are the field of scholarly discourse among the scholars of Islam۔ Some modern scholars have rejected these hadiths saying that they are not proven by reliable sources, but authentic Islamic researchers of the past and present accepted these hadiths and did not consider the attitude of authenticating them to be correct. If viewed objectively, it is the second attitude that is correct. However, what was the reason for this prohibition of Prophet Muhammad (may Allah bless him and grant him peace), is another dilemma that occurred to Islamic scholars in this chapter, from the great commentator of hadith, Hafiz Ibn Hajar Asqalani, to the famous historian of the recent past, Shibli Nomani, they seem confused in this debate and they could not give any proper justification for this prohibition. In this paper, the author has clarified the authentic position of the relevant hadiths and also discussed their correct justification. And it has been stated that the reason for this prohibition is very clear and unambiguous, which is clearly indicated by the words of the relevant hadiths themselves. Also, what should be the right attitude in terms of rejecting or accepting the Bible quotes, in some of the Prophetic hadiths, there are some manners and points mentioned in this regard, which, unfortunately, are badly neglected by some modern Muslim writers. Thus, they reflect an unmoderate attitude of denial or acception when speaking from the Bible. The author also mentions his correspondence with the editors of some religious magazines in which some of his irresponsible comments regarding the Bible were criticized.